2020
DOI: 10.1111/ppc.12708
|View full text |Cite
|
Sign up to set email alerts
|

Examination of evidence‐based nursing attitudes and the relationship with professional self‐concept in nurses working in a psychiatric hospital

Abstract: The study was carried out with nurses working in a psychiatric clinic to examine their attitudes toward evidence-based practices and levels of professional self-concept.Design and Methods: This study was carried out using a descriptive and correlational search design. We used a Personal Information Form developed by the authors and Evidence-Based Nursing Attitude Scale (EBNAS) and Professional Self-Concept Scale for Clinical Nurses (PSCSCN) to obtain data. Percentages and averages, and the Pearson correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The concept significantly influences nurses' capacity to deliver high-quality care and achieve positive health outcomes [10]. A robust professional self-concept enhances nurses' adaptation to real-world challenges, fosters their accountability, and supports evidence-based practice [11][12][13]. Evidence supports that nurses with strong professional self-concept experience higher levels of self-esteem, self-efficacy, and overall well-being, contributing positively to their mental health and coping with professional and daily life challenges [14].…”
Section: Introductionmentioning
confidence: 99%
“…The concept significantly influences nurses' capacity to deliver high-quality care and achieve positive health outcomes [10]. A robust professional self-concept enhances nurses' adaptation to real-world challenges, fosters their accountability, and supports evidence-based practice [11][12][13]. Evidence supports that nurses with strong professional self-concept experience higher levels of self-esteem, self-efficacy, and overall well-being, contributing positively to their mental health and coping with professional and daily life challenges [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that evidence-based care can serve as a framework for decisionmaking in specific patient situations, leading to providing safe and cost-effective care, and increasing patient satisfaction, and the selfconfidence of nurses (Liu et al, 2021;Sedgwick et al, 2014). It has also been described as one of the determining factors of nursing professionalism (Asi Karakaş et al, 2021). lor, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses with high professional self-concept are more accountable for their patients [ 12 ] and work outcomes and see patients more respectfully and interestedly [ 13 ]. It is also worth mentioning that high professional self-concept positively influences the acceptance and demand for evidence-based practice in nursing [ 14 ].…”
Section: Introductionmentioning
confidence: 99%